2017
DOI: 10.1002/cjoc.201600615
|View full text |Cite
|
Sign up to set email alerts
|

High Glass Transition of Fluorinated Polyimides Derived from 4‐(3,4‐Difluorophenyl)‐2,6‐bis(4‐aminophenyl)pyridine

Abstract: A series of novel fluorinated polyimides (PIs) were prepared from 4-(3,4-difluorophenyl)-2,6-bis(4-aminophenyl)pyridine (FPAP) and commercial aromatic dianhydrides via conventional two-step thermal imidization technique. The structure of the monomer was confirmed by FT-IR, NMR, and mass spectrometry. All of the obtained PIs were studied with FT-IR, TGA, DSC, WAXD and contact angles analysis. These results showed that polymer materials presented excellent thermal properties with the glass transition temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…via nitrification and reduction, as we previously described. 31 The specific steps of the synthesis and the results of the characterization data are described in the supporting material (Scheme S1, Figure S1 to S5).…”
Section: Monomer Synthesismentioning
confidence: 99%
“…via nitrification and reduction, as we previously described. 31 The specific steps of the synthesis and the results of the characterization data are described in the supporting material (Scheme S1, Figure S1 to S5).…”
Section: Monomer Synthesismentioning
confidence: 99%
“…In general, the introduction of rigid heteroaromatic pyridine ring into the polymer chain could endow aromatic polyimides with excellent thermal stability. 35 37 Guan et al 37 reported a series of polyimides containing pyridine and sulfur units with outstanding thermal stability, excellent mechanical, and good optical properties.…”
Section: Introductionmentioning
confidence: 99%